2015
DOI: 10.1515/hsz-2014-0257
|View full text |Cite
|
Sign up to set email alerts
|

Ras activation revisited: role of GEF and GAP systems

Abstract: Ras is a prototypical small G-protein and a central regulator of growth, proliferation and differentiation processes in virtually every nucleated cell. As such, Ras becomes engaged and activated by multiple growth factors, mitogens, cytokines or adhesion receptors. Ras activation comes about by changes in the steady-state equilibrium between the inactive guanosine diphosphate (GDP)-bound and active guanosine triphosphate (GTP)-bound states of Ras, resulting in the mostly transient accumulation of Ras-GTP. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 108 publications
2
74
0
Order By: Relevance
“…RAS-effector interaction essentially requires RAS association with membranes [25] and its activation by specific regulatory proteins ( e . g ., guanine nucleotide exchange factors or GEFs), leading to the formation of GTP-bound, active RAS [26,27,28]. Notably, RAS proteins change their conformation mainly at two highly mobile regions, designated as switch I (residues 30–40) and switch II (residues 60–68) [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…RAS-effector interaction essentially requires RAS association with membranes [25] and its activation by specific regulatory proteins ( e . g ., guanine nucleotide exchange factors or GEFs), leading to the formation of GTP-bound, active RAS [26,27,28]. Notably, RAS proteins change their conformation mainly at two highly mobile regions, designated as switch I (residues 30–40) and switch II (residues 60–68) [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…RAS proteins respond to extracellular signals and transform them into intracellular responses through interaction with effector proteins. The activity of RAS proteins is highly controlled through two sets of specific regulators with opposite functions, the guanine nucleotide exchange factors and the GTPase-activating proteins (GAPs), as activators and inactivators of RAS signaling, respectively (18). In the present study, we analyzed the expression profile of different Ras isoforms in HSCs and found embryonic stem cell-expressed RAS (ERas) specifically expressed in quiescent HSCs.…”
mentioning
confidence: 98%
“…This result confirms previous findings for T cells 22,23 and suggests that immune cells that express RasGRP family members (RasGRP4 in U937 and RasGRP1 in Jurkat and human primary T cells; Roose et al . 17 ) have exceptionally high basal rates of nucleotide exchange on Ras (some 30-fold higher than the intrinsic exchange rate of Ras 24 ) (Figure 6d). …”
Section: Resultsmentioning
confidence: 99%
“…This mode of GTPase activation, that is, via receptor-induced inactivation of GAP, has been recently shown for Rheb, a Ras-related GTPase, and some evidence points out that it may also be the case for Ras (reviewed in Hennig et al . 24 and Laplante and Sabatini 27 ). It has previously been shown that certain growth factors such as platelet-derived growth factor or epidermal growth factor induce proteolytic degradation of NF1, one of the RasGAPs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation